2012
DOI: 10.1684/agr.2012.0598
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of conversion to drip irrigation systems by farmers: The case of the Mitidja plain in Algeria

Abstract: Les déterminants de l'adoption du système d'irrigation par goutte-à-goutte par les agriculteurs algériens de la plaine de la Mitidja Résumé Durant la dernière décennie, l'Algérie a encouragé l'adoption de techniques d'irrigation plus économes en eau, comme l'irrigation par goutte-à-goutte, en subventionnant les agriculteurs grâce à un plan national de développement agricole. Cette initiative n'a connu le succès qu'auprès d'un nombre restreint d'agriculteurs. L'objectif de l'article est d'identifier les détermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Indeed, the survey showed that conversion to drip irrigation by farmers is mainly driven by social and cultural reasons related to higher convenience in daily tasks as drip irrigation is an automated and less time‐consuming technique. Another social reason motivating farmers for drip irrigation adoption is the access to subsidies, opportunities to create alliances, and modernization of infrastructures, which is coherent with conclusions of previous studies mentioned in discussion of the results (Berbel & Mateos, 2014; Salhi et al, 2012; Wanvoeke et al, 2016). Results of this work denote the divergence between decision makers objectives in national plans of irrigation conversion like NIWSP in Morocco (water saving) and farmers objectives.…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, the survey showed that conversion to drip irrigation by farmers is mainly driven by social and cultural reasons related to higher convenience in daily tasks as drip irrigation is an automated and less time‐consuming technique. Another social reason motivating farmers for drip irrigation adoption is the access to subsidies, opportunities to create alliances, and modernization of infrastructures, which is coherent with conclusions of previous studies mentioned in discussion of the results (Berbel & Mateos, 2014; Salhi et al, 2012; Wanvoeke et al, 2016). Results of this work denote the divergence between decision makers objectives in national plans of irrigation conversion like NIWSP in Morocco (water saving) and farmers objectives.…”
Section: Discussionsupporting
confidence: 86%
“…Algeria ( 8) Badaoui et al, 2019;Bouzid et al, 2020;Daoudi and Lejars, 2016;Difallah et al, 2017;Khaled and Segni, 2016;Naouri et al, 2015;Naouri et al, 2020;Salhi et al, 2012 Egypt (6) Ghareeb and Seif, 2020;Hamad et al, 2020;Abbassy and Ead, 2020;Le and Dhehibi, 2019;Stilt, 2018;Zahran et al, 2020 Morocco ( 6) Ameur et al, 2013;Badraoui et al, 2020;Bouissil et al, 2020;Codron et al, 2007;Fouad et al, 2018;Labbaci et al, 2015 Tunisia ( 7) Aziza et al, 2009;Ben Rejeb et al, 2020;Braiki et al, 2018;Callieris et al, 2016;Dhraief et al, 2019;Dolinska, 2017;Souli et al, 2020 North Africa* ( 2 (cf. marketing/consumption) and intermediate stages (e.g.…”
Section: Country or Region (Number Of Articles) Referencesmentioning
confidence: 99%
“…packing, processing) are generally overlooked. Regarding production, the selected documents focus, among others, on water resources management and irrigation (Ameur et al, 2013;Difallah et al, 2017;Ghareeb and Seif, 2020;Jovanovic et al, 2020;Kuper et al, 2009;Le and Dhehibi, 2019;Naouri et al, 2020;Narvarte et al, 2018;Salhi et al, 2012) and pest management (Bouissil et al, 2020). Some articles take a more holistic approach and deal with different types of innovative practices.…”
Section: Country or Region (Number Of Articles) Referencesmentioning
confidence: 99%
See 2 more Smart Citations